A review on factors affecting drying process of pistachio and their impact on product’s quality. - Abbas, Kassim Ali; Saleh, A. M.; Lasekan, Olasegun; Khalil, Sahar K. (Canadian Center of Science and Education, 2010)
This review is focusing on the parameters affecting the quality of pistachio during hot-air drying process. Accordingly, the various common existing processing methods are reviewed extensively using the current literature to investigate the latest developments in this regard. The findings revealed that both of the type of method used as well as the parameters controlling the drying rate, have different impacts on final product’s quality. The study concluded that the sun drying method has the best final quality as well as to lowest energy cost. This study provides a guide for the food technologist to the select the optimum method by which the best quality can be produced and minimum energy can be spent.